Relationship among Higher Education Students’ Research Attitudes, Anxiety, and Self-Efficacy - Amjad, Nimra; Naseem, Afshan (Pakistan Languages and Humanities Review, 2025)
The study deals with the relationship that exists between research attitude and research anxiety and research self-efficacy among undergraduate students in Lahore studying in both the public and private universities. The researchers used a survey design approach. Simple random selection together with convenience sampling was used for selecting the 500 participants. Three scales were used for the study. Reliability was ensured through pilot testing whereas validity through subject experts. Pearson correlation coefficient (r) was applied for analysis. Findings revealed that research attitude along with research anxiety and research self-efficacy had shown positive relations. Research self-efficacy showed moderate and significant positive relationship with research attitude. It is recommended that the workshops and seminars should be planned not only to share the value and significance of research but also to give practical training and students an opportunity to feel successful in using research in current activities.